Burned to ashes : How the thermal decomposition of refractory organics in the inner protoplanetary disc impacts the gas-phase C/O ratio - Houge, Adrien; Johansen, Anders; Bergin, Edwin; Ciesla, Fred J.; Bitsch, Bertram; Lambrechts, Michiel; Henning, Thomas; Perotti, Giulia (Astronomy and Astrophysics, 2025)
The largest reservoir of carbon in protoplanetary discs is stored in refractory organics, which thermally decompose into the gas phase at the organics line located well into the interior of the water iceline. Because this region is so close to the host star, it is often assumed that the released gaseous material is rapidly accreted and has little effect on the evolution of the disc composition. However, laboratory experiments have shown that the thermal decomposition process is irreversible, breaking macromolecular refractory organics into simpler, volatile carbon-bearing compounds. As a result, unlike the iceline of other volatiles, which traps vapor inwards due to recondensation, the organics line remains permeable, allowing gaseous carbon to diffuse outwards without returning to the solid phase. In this paper, we investigate how this process affects the disc composition, particularly the gas-phase C/H and C/O ratios, by incorporating it into a 1D evolution model for gas and solids and assuming refractory organics dominantly decompose into C2H2. Our results show that this process allows this carbon-rich gas to survive well beyond the organics line (out to 7 au around a solar-mass star) and for much longer timescales such that its abundance is increased by an order of magnitude. This has several implications in planet formation, notably by altering how the composition of solids and gas relate and regarding the fraction of heavy elements available to giant planets. In the framework of our model, refractory organics significantly in`uence the evolution of the gas-phase C/O ratio, which may help interpret measurements made with Spitzer and JWST.
Keywords: planets and satellites: composition; planets and satellites: formation; protoplanetary disks